Small Claims : Where Does Serbia Stand? A Comparative Analysis - World Bank (World Bank, Washington, DC, 2020)
Evidence suggests that poor court performance negatively affects the economy. Complaints about the business climate are often associated with complicated procedural laws and backlogs that beleaguer the system and slow it down. According to the European Commission for the Efficiency of Justice (CEPEJ) 2018 report, it takes on average 315 days to resolve a civil and commercial case in a first instance court in Serbia.1 This is well above the EU average of 233 days. Small value cases that get stuck in Serbia’s Basic Courts perpetuate backlogs, hamper access to justice and consume a disproportionate amount of judicial resources relative to the value of these cases. This report provides a comparative analysis of the procedure for resolving small claims in Serbia and recommendations to improve it, based on lessons learned from comparator jurisdictions: Austria, Denmark, Estonia, Germany, Latvia and Slovenia. The report was developed under the Multi-Donor Trust Fund for Justice Sector Support in Serbia (MDTF-JSS) and is informed by a broader World Bank initiative to support justice policy dialogue and reform in the Western Balkans. The analysis is primarily intended for the legal community in Serbia, including policy makers, judges, lawyers and those in academia.